2022
DOI: 10.3847/1538-3881/ac5b73
|View full text |Cite
|
Sign up to set email alerts
|

The Many-faceted Light Curves of Young Disk-bearing Stars in Taurus as Seen by K2

Abstract: We present a comprehensive study of the variability properties of young disk-bearing stars in the Taurus star-forming region, paralleling our previous investigation in ρ Oph and Upper Sco. A sample of 99 confirmed Taurus association members is placed in the diagnostic Q − M plane of flux asymmetry (M) and (Q), which guides our assignment of variability classes. We find a similar proportion of flux-symmetric variables in Taurus, but more bursters and fewer dippers relative to Upper Sco. The regions also differ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 73 publications
(97 reference statements)
5
21
0
Order By: Relevance
“…We have classified 323 stars using the Q − M variability plane, to quantify flux asymmetry and waveform repeatability in the light curves. This ratio is similar to that in Taurus with 70% and 30%, respectively (Cody et al 2022). 5.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…We have classified 323 stars using the Q − M variability plane, to quantify flux asymmetry and waveform repeatability in the light curves. This ratio is similar to that in Taurus with 70% and 30%, respectively (Cody et al 2022). 5.…”
Section: Discussionsupporting
confidence: 84%
“…There is some expectation that the light-curve morphological classes could correlate with infrared excess. Using K2 data sets, several previous studies, namely Cody & Hillenbrand (2018) in Oph/Sco, Cody et al (2022) in Taurus, and Venuti et al (2021) in the Lagoon Nebula all found that both the periodic (P) and the QPS sources tend to have lower values of infrared excess on average, and in fact dominate the source population at small infrared color values. This is consistent with a relatively clean line of sight to the spotted stellar photosphere, and a lack of accretion effects in the light curve.…”
Section: Correlation Of Variability Properties With Infrared Excessmentioning
confidence: 99%
See 3 more Smart Citations